Dielectrical and electro-mechanical behavior of NBR at high electric field strength. (October 2020) - Vennemann, N.; Kummerlöwe, C.; Mertes, M.; Kühnast, F.; Bröker, D.; Siebert, A.
Abstract: The aim of this work is to present a new approach to characterize the dielectric properties of elastomers especially at low frequencies and high electric field strength, close to the operating conditions of dielectric elastomer actuators (DEA). By means of an electro-rheological measuring cell, static (DC) and alternating (AC) high electric field strength were applied to different types of acrylonitrile-butadiene rubbers (NBR), with varying content of polar acrylonitrile groups. Based on fundamental theory of electricity complex permittivity and polarization were calculated from Coulomb stress measurements at varying frequencies. During high voltage measurements it was observed, that dielectric loss current increases, if a certain critical field strength is exceeded. It is shown, that polar NBR rubbers exhibit a critical field strength far below of the non-polar polybutadiene rubber (BR), acting as a reference sample. NBR exhibits extraordinary high permittivity at low frequency, which makes this material as a favorite candidate for DEA. Furthermore, mechanical properties of NBR can be easily altered by application of an alternating electric field. This phenomenon opens new opportunities in a great variety of applications. Highlights: New approach to characterize the dielectric properties of elastomers is presented. Complex permittivity and polarization of NBR were determined by means of Coulomb stress measurements. NBR exhibits extraordinary high permittivity at low frequency, which makes this material as a favorite candidate for DEA. Excitation of DEA with an oscillating electric field results in Coulomb stress distorted by superimposed higher harmonics. Mechanical properties of NBR can be altered easily by application of a high electric field.